2023
DOI: 10.3390/molecules28186608
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Lactation Stage on the Metabolite Composition of Bovine Milk

Claire Connolly,
Xiaofei Yin,
Lorraine Brennan

Abstract: Bovine milk is a nutrient-dense food and a major component of the human diet. Therefore, understanding the factors that impact its composition is of great importance. Applications of metabolomics provide in-depth analysis of the metabolite composition of milk. The objective of this research was to examine the impact of lactation stage on bovine milk metabolite levels. Metabolomic analysis of bovine milk powder samples across lactation (N = 18) was performed using nuclear magnetic resonance (1H-NMR) spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…The freezing point indicator was slightly negative, and the content of somatic cells is slightly positively associated with the day of lactation. The data obtained were consistent with research (Connolly et al, 2023) on the influence of the lactation stage on the level of milk yield and milk quality indicators.…”
Section: Source: Compiled By the Authorssupporting
confidence: 89%
See 1 more Smart Citation
“…The freezing point indicator was slightly negative, and the content of somatic cells is slightly positively associated with the day of lactation. The data obtained were consistent with research (Connolly et al, 2023) on the influence of the lactation stage on the level of milk yield and milk quality indicators.…”
Section: Source: Compiled By the Authorssupporting
confidence: 89%
“…The main criteria for milk quality that the EU pays attention to are total bacterial count, somatic cell count, freezing point, fat and protein content. Thus, using the multi-platform approach, C. Connolly et al (2023) found that the metabolomic profile of cow milk at the beginning of lactation is markedly different from that in the middle and end of lactation. R. This fact is confirmed by studies of the first streams of milk, in which the fat content is lower, and the protein content is higher.…”
Section: Source: Compiled By the Authorsmentioning
confidence: 99%
“…The freezing point indicator was slightly negative, and the content of somatic cells is slightly positively associated with the day of lactation. The data obtained were consistent with research (Connolly et al, 2023) on the influence of the lactation stage on the level of milk yield and milk quality indicators.…”
Section: Source: Compiled By the Authorssupporting
confidence: 89%
“…Connolly et al (2023) found that the metabolomic profile of cow milk at the beginning of lactation is markedly different from that in the middle and end of lactation. R.Feliciano et al (2023) established seasonal patterns of milk quality indicators (fat and protein content) in different weather conditions throughout the year.…”
mentioning
confidence: 97%